Knowledge, attitudes, and practices on urinary schistosomiasis among schoolchildren in Ethiopia: cross-sectional study - Ketema Deribew; Delenasaw Yewhalaw; Zeleke Mekonnen (Journal of Health, Population and Nutrition)
Abstract Background Urinary schistosomiasis is a disease caused by Schistosoma haematobium and is one of the public health problems in Ethiopia. When developing specific schistosomiasis control intervention program, the existing knowledge, attitudes and practices (KAPs) must be taken into account. This study aimed to assess the KAPs of primary schoolchildren towards urinary schistosomiasis in Ethiopia. Methods A total of 1171 study participants aged 5 to 15 years were selected randomly. Results Of the 1171 interviewed schoolchildren, 654, or 55.8%, said they had heard of urinary schistosomiasis. Using river or dam water for household consumption had association with urinary schistosomiasis infection history (P = 0.001). Logistic regression analysis showed that males had higher risk of getting urinary schistosomiasis infection compared to females (OR = 3.01, P < 0.001). Children in low socio-economic status had higher risk of having urinary schistosomiasis compared to high socio-economic status (OR = 2.81, P < 0.001). Compared to urban dweller, children in rural area had higher risk of having urinary schistosomiasis (OR = 4.34, P < 0.001). Respondents who used river water (OR = 2.48, P = 0.005) and lake or dam water (OR = 3.33, P = < 0.001) were at higher risk of urinary schistosomiasis infection. Furthermore, respondents swimming or playing in river water had higher risk of urinary schistosomiasis infection history (OR = 1.62, P = 0.005). Conclusions There was knowledge gap in schoolchildren about urinary schistosomiasis causes, transmission, symptoms and prevention. Therefore, appropriate health education and behavioral change intervention is needed to create better knowledge and practices in children to prevent and control urinary schistosomiasis. Health organizations and policy makers should contribute to improve knowledge at the school as well as community level.